2012
DOI: 10.4308/hjb.19.4.183
|View full text |Cite
|
Sign up to set email alerts
|

Application of Two Molecular Sexing Methods for Indonesian Bird Species: Implication for Captive Breeding Programs in Indonesia

Abstract: Visually identifying the sex of a bird can be difficult. It cannot be done in half the world's species when they are adults, and virtually none can be sexed as chicks. Despite this, the sex of a bird is vital for captive breeding. An increased number of birds are being sexed using DNA amplification techniques. In this approach, the CHD-W and CHD-Z are distinguished by the amplification of an intron present in both genes. PCR products on the gel electrophoresis vary in size revealing one band in males at the CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
2
25
0
1
Order By: Relevance
“…Bird sex can be ascertained from the CHD-W gene using the Po primer and multiplex PCR methods [16], and real-time PCR [14]. Sex identification of birds for breeding purposes may use the P8/P2 primer on the CHD gene for the two sex chromosomes, W and Z [17]. Three primers: HD1F/CHD1R, 2550F/2718R, and P2/P8 are used to determine the sex of birds [18]; PCR methods are more accurate than morphometry and DNA finger-printing for sex identification in birds [19].…”
Section: Introductionmentioning
confidence: 99%
“…Bird sex can be ascertained from the CHD-W gene using the Po primer and multiplex PCR methods [16], and real-time PCR [14]. Sex identification of birds for breeding purposes may use the P8/P2 primer on the CHD gene for the two sex chromosomes, W and Z [17]. Three primers: HD1F/CHD1R, 2550F/2718R, and P2/P8 are used to determine the sex of birds [18]; PCR methods are more accurate than morphometry and DNA finger-printing for sex identification in birds [19].…”
Section: Introductionmentioning
confidence: 99%
“…That said, the amplified sex specific region revealed some divergence between the Anglesea population and the Piccadilly Circus populations, suggesting that mutations could occur in the primer sites of some populations/taxa, limiting the generality of the sex- linked markers. The identification of sex-specific sequence has important practical value in many contexts, including ecological studies [63][64][65], conservation of threatened or endangered species [66][67][68][69], captive breeding [70], aquaculture [71,72], elimination of mortality as a possible explanation for sex ratio bias [32,73] sex forensics [74] and identifying genotypic sex [32,75,76] or in studies of early developmental processes where sex of the developing embryo is important [77,78]. Two approaches for identifying sex linked markers using whole genome sequencing seem appropriate, both relying on the divergence of the X and Y homologues in the region of recombination suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Different primer sets based on the CHD1 gene have been used to sex birds [26,2830]. We chose two that have been successful in many passerines [27] and introduced minor modifications to their sequences.…”
Section: Discussionmentioning
confidence: 99%
“…CHD1 is a highly conserved gene, which makes it a candidate for universal non-ratite avian sex identification. A number of studies have reported specific PCR primers to screen the intron variants of the Z and W alleles and have successfully applied these to many avian species [2630]. The difference between the size of the male and female fragments vary between species and primer pairs.…”
Section: Introductionmentioning
confidence: 99%